Cutaneous panarteritis as a Iate manifestation of the erythema nodosum leprosum - Fleury, Raul Negrão (1999)
The authors studied 11 cases of multibacillary Hansen's disease (9 lepromatous and 2 borderlinelepromatous) with late erythema nodosum leprosum manifestations. The systemic symptoms were mild and there was low number of cutaneous lesions in lower limbs. Histologically, those lesions presented necrotizing and exsudative segmental arteritis in the deep dermis, with discrete inflammatory reaction in the neighboring dermis and sub-cutis. There were discrete or absent evidences of previous involvement by Hansen's disease, however, in seven patients, acid fast bacilli were found on the wall of involved vessels. Probably there are pathogenic similarities between these arteritis and the necrotizing vasculitis that occurs in severe and generalized episodes of erythema nodosum leprosum throughout specific treatment due to persistence of mycobacterial antigen on the vessel wall, even after their elimination from other cutaneous sites. The eventual exposure of mycobacterial antigens would stimulate immune complex formation and acute inflammatory and necrotizing reaction. In addition, the histolopathological and even clinical aspects of these arteritis are very similar toThese clinical and structural similarities may correspond to similar pathogenic mechanisms between the two cutaneous vasculitis.